Comparison of The Learning Outcomes of Junior High School Students Utilizing Audio-Visual and Chart Learning Media to Study Ecosystem - Afriza, Dedy Afriza; Nasution, Nanda Eska Anugrah (Aspirasi Masyarakat Intelektual Islam Nusantara, 2022)
Teachers require knowledge pertaining to which types of learning media are most effective for teaching certain concepts in scientific disciplines. The audio-visual learning media and two-dimensional charta learning media may be utilized to aid instructors in educating junior high school pupils about ecosystems. This research seeks to compare the use of audio-visual learning media with two-dimensional charta learning media to educate junior high school students of Negeri 2 Babalan about ecosystems. The method of study used was quasi-experimental, and the research sample consisted of two classes of eight seventh-graders from SMP Negeri 2 Babalan, chosen via cluster random sampling. The research instrument was a multiple-choice test of cognitive learning outcome. The average value for the biology learning outcomes of seventh-grade SMP Negeri 2 Babalan students who are taught ecosystem topics via audiovisual learning media is 79.26, and for the class who are taught ecosystem topics through chart learning media is 73.47. The results demonstrate that there is a significant difference between the learning outcomes of class VII SMP Negeri 2 Babalan students using audiovisual media and chart media for ecosystem materials. This research concludes that the use of audiovisual learning media by junior high school instructors to teach ecological content is superior than the use of charta media in terms of the cognitive learning results of students.